Space State on Earth and Beyond: Philosophy, Models,Experience and Prospects - Krichevsky, S.; Udartsev, S. (Philosophy and Cosmology, 2019)
The article discusses the philosophical, legal, historical, and technological aspects of the space state, provides definitions, presents classifications, models, suggests examples, and makes forecasts. The general classification of participants in space activities for the purpose of survival and development, as well as the universal classification of space states have been developed. The definitions of space states are given, criteria for classifying space states into different levels and types are proposed, considering the areas and scope of space activities, and their various forms are shown. The prospects and limitations of the space states, their philosophical and technological aspects, including those in the new era of international cooperation, taking into account the possibilities of creating the World Cosmic Union, are briefly reviewed, as well as the futurological aspect of a universal space state is considered. The main conclusions and recommendations are formulated.
Keywords: space state; space activities; cosmic civilization; cosmic humanity; classification; model; philosophy of state and law; digital space state Asgardia; evolution; Research Subject Categories::LAW/JURISPRUDENCE